Resilience imperative : uncertainty, risks and disasters - Reghezza-Zitt, Magali; Rufat, Samuel (London : ISTE Press, 2015)
"We have to adapt to the impacts that, unfortunately, we can no longer avoid", said President Obama at the UN Climate Summit in September 2014. Adaptation and resilience are now a must in both academic research and international bodies. A fashionable concept, resilience's polysemy sparks many debates on its uses and operational relevance. This book bridges the increasing divide between academic research and the latest planning innovations, offering practical and conceptual insights for practitioners, researchers and students. Magali Reghezza-Zitt and Samuel Rufat present a cross-disciplinary, state-of-the-art debate and critical analysis of the social, spatial, practical and political implications of resilience.
Chapter 9: (Re)Constructing Resilient Districts: Experiences Compared9.1. (Re)New Orleans: Big Easy as a Resilience Laboratory; 9.2. Urban Renewal and Resilience in East London: The Thames Gateway; 9.3. Conclusion; 9.4. Bibliography; Chapter 10: Resilience, Memory and Practices; 10.1. The Resilient System Between Identity and Evolution; 10.2. Resilience and Retaining a Memory of Risk; 10.3. The Problem of Identity; 10.4. Conclusion; 10.5. Bibliography; Chapter 11: Critique of Pure Resilience; 11.1. Resilience to the Test of Discourses; 11.2. The Dark Side of Resilience.
Online resource; title from PDF title page (EBSCO, viewed October 14, 2015).
Includes bibliographical references and index.
Keywords: Emergency management; Disaster relief; BUSINESS & ECONOMICS -- Infrastructure; SOCIAL SCIENCE -- General; Disaster relief; Emergency management; Disaster Planning -- organization & administration; Risk Management -- organization & administration; Social Planning; Social Control Policies; Electronic books; Electronic book